Bioefficacy and phytotoxicity evaluation of Metiram 70% WG: A new fungicide molecule against anthracnose disease of chilli caused by Colletotrichum capsici - Saha, Poly; Bera, Soumen (Indian Journal of Plant Protection, 2019)
Chilli (Capsicum annum L.) universally known as wonder spice and one of the most economical spice crops grown all over the world. Major production constraints have been identified as anthracnose disease caused by Colletotrichum capsici (Syd.) Butler and Bisby known to affect the yield and quality of fruits during both mature and post-harvest storing condition. Chemicals being the only feasible means of controlling the disease with quick knock down effect, researchers are in continuous effort to find the new molecules that can be used alternatively with the existing chemicals to reduce not only the chance of development of fungicide resistance but also be environment friendly. Keeping in mind, the time required for developing resistant varieties and environment safety issue, an experiment was formulated with a new molecules Metiram 70% WG to find out its field efficacy and phytotoxicity even at higher doses. The experiment was conducted by taking a susceptible chilli variety Bullet during Kharif season of 2017 and 2018 under natural epiphytotic condition though pathogenicity of the pathogen was proved under laboratory condition. Result revealed that Metiram 70% WG 1400g a.i /ha with ultimate PDI score 9.93 was the most effective followed by Metiram 70% WG 1050 g a.i /ha with PDI 10.69 in controlling the disease and showed 60.70% and 57.69% reduction in disease over untreated control respectively. Pooled data analysis on fruit yield showed the similar results with incremental yield of 91.70% and 76.77% for Metiram 70% WG 1400g a.i / ha and Metiram 70% WG 1050 g a.i /ha over untreated control correspondingly. Metiram at higher doses did not show any phytotoxicity symptoms on the crop. Thus, the new molecule metiram 70% WG would be recommended as an integral part of integrated resistance management programmes in chilli.